Evolution of untreated calf deep-vein thrombosis in high risk symptomatic outpatients: the blind, prospective CALTHRO study - Palareti, Gualtiero; Cosmi, Benilde; Lessiani, Gianfranco; Rodorigo, Giuseppina; Guazzaloca, Giuliana; Brusi, Carlotta; Valdré, Lelia; Conti, Eleonora; Sartori, Michelangelo; Legnani, Cristina (Thrombosis and haemostasis, 2010)
The natural history of calf deep-vein thrombosis (DVT) is still uncertain and it is debated whether it warrants to be diagnosed and treated. We aimed to investigate the complication rate of untreated isolated calf DVT (ICDVT). Symptomatic outpatients were prospectively managed with serial compression ultrasonography (SCUS). Those without proximal DVT and with likely pre-test clinical probability (PCP) or altered D-dimer received immediate subsequent complete examination of calf deep veins (CCUS) by a different operator. The result of CCUS was kept blind both to the managing doctor and the patient and disclosed after three months. Primary outcome was the rate of venous thromboembolism at three months. We examined 431 subjects (196 males; median age 68.0 years) in whom five outcomes were recorded (1.2%; 95% confidence intervals [CI]: 0.4-2.7). If CCUS results had been available, outcomes would have been recorded in 3/424 patients (0.7%; 95% CI: 0.2-2.1) with two events in subjects negative at both serial and complete CUS. ICDVT was diagnosed in 65 subjects (15.3%; 95% CI: 12-19); of whom 59 remained uneventful (one was lost to follow-up). A significant higher rate of outcomes was recorded in subjects with than without ICDVT (5/64; 7.8%; 95% CI: 3-17 vs. 3/351; 0.8%; 95% CI: 0-2; p=0.003). However, after excluding two events picked at serial CUS in subjects with ICDVT, the difference became barely significant (3/64; 4.7%; 95% CI: 1-13; p=0.049). Thrombotic evolution of untreated ICDVT in high-risk subjects may be relevant. Larger studies are needed to address this issue.